2011
DOI: 10.1107/s1600536811019532
|View full text |Cite
|
Sign up to set email alerts
|

2′-Chloro-4-methoxy-3-nitrobenzil

Abstract: In the title compound, C15H10ClNO5, the dihedral angle between the aromatic rings is 87.99 (5)°. The O—C—C—O torsion angle between the two carbonyl units is −119.03 (16)°. The crystal structure is stabilized by a weak intermolecular C—H⋯O hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…By this technique, it is also possible to find a new drug and also prepare new synthetic compounds and lead molecules with different mechanisms and thereby different target organisms, especially against drugresistant bacteria and emerging microbes. For the purpose, three different substituted benzil compounds have been synthesized, characterized, and evaluated their capabilities in biological activity [14][15][16][17][18][19][20][21][22][23]. From the literature survey, it had been found that benzil has antitumor activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…By this technique, it is also possible to find a new drug and also prepare new synthetic compounds and lead molecules with different mechanisms and thereby different target organisms, especially against drugresistant bacteria and emerging microbes. For the purpose, three different substituted benzil compounds have been synthesized, characterized, and evaluated their capabilities in biological activity [14][15][16][17][18][19][20][21][22][23]. From the literature survey, it had been found that benzil has antitumor activity [24].…”
Section: Introductionmentioning
confidence: 99%